Xilinx (FPGA) design for single phase DC-AC matrix converter with sinusoidal pulse width modulation (SPWM) / Mohd Raduan Md Adam - Md Adam, Mohd Raduan (2003)
This project illustrates the design and development of synchronous pulse-width modulation (SPWM) generator suitable to control the single phase matrix converter. The SPMC as a direct frequency changer were used in this work. The SPMC circuit composed from four ideal power switches used as a frequency converter. The desire output voltage will be synthesized using SPWM technique. The target of this project is to generate the Sinusoidal Pulse-width Modulation switching Pattern using Xilinx FPGA that is suitable to control the single-phase matrix converter. One sine waveform with one carrier waveforms is used to generate the PWM. The PWM pattern proposes occupies less FPGA block cell hence more space could be used for other control algorithm. Results are provided to demonstrate the effectiveness of the design. Using Pspice and MATlab/Simulink showed the behavior of matrix converter operation. While the Xilinx FPGA show the result of SPMC using SPWM pattern.